CHARACTERISTICS OF THE FORM OF THE EYE IN THE COURSE OF MIGRAINE ATTACKS - Pulatov, M.Q. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This article discusses the results of clinical observation of the degree of occurrence and the specificity of symptoms of the eye form, which is a subtype of migraine that affects almost 15% or one billion people worldwide.